Circulating Cytokines and Growth Factors in Acute Cerebral Large Vessel Occlusion—Association with Success of Endovascular Treatment - Grosse, Gerrit M.; Werlein, Christopher; Blume, Nicole; Abu-Fares, Omar; Götz, Friedrich; Gabriel, Maria M.; Ernst, Johanna; Leotescu, Andrei; Worthmann, Hans; Kühnel, Mark P.; Jonigk, Danny D.; Falk, Christine S.; Weissenborn, Karin; Schuppner, Ramona (Thrombosis and Haemostasis, 2021)
Mechanical thrombectomy (MT) is a highly efficient treatment in patients with acute ischemic stroke due to large vessel occlusion (LVO). However, in a relevant proportion of LVO, no sufficient recanalization can be achieved. The composition of cerebral thrombi is highly heterogeneous and may constitute a relevant factor for insufficient reperfusion. We hypothesized that circulating cytokines and growth factors involved in thromboinflammation and platelet activation may be associated with reperfusion status and thrombus composition in patients undergoing MT. An according biomarker panel was measured in plasma specimens taken prior to MT and at a 7-day follow-up. The reperfusion status was categorized into sufficient or insufficient. The composition of retrieved thrombi was histologically analyzed. Differences of baseline biomarker concentrations between insufficient and sufficient reperfusions were highest for interferon (IFN)-γ, epidermal growth factor, platelet-derived growth factor (PDGF)-AB/BB, and IFN-γ-induced protein 10 (IP-10/CXCL10). After applying correction for multiple comparisons and logistic regression analysis adjusting for stroke etiology, intravenous thrombolysis, and vascular risk factors, PDGF-AB/BB was identified as an independent predictor of reperfusion status (odds ratio: 0.403; 95% confidence interval: 0.199–0.819). Histological analysis revealed that the majority of thrombi had a mixed composition. In conclusion, this study provides the first evidence that cytokines and growth factors are potential effectors in patients undergoing MT for the treatment of acute ischemic stroke.
Keywords: cytokines; growth factors; ischemic stroke; large vessel occlusion; mechanical thrombectomy